2001
DOI: 10.1007/s004060170057
|View full text |Cite
|
Sign up to set email alerts
|

Increased prevalence of obesity in narcoleptic patients and relatives

Abstract: Increased Body Mass Indices (BMIs), increased prevalences of non insulin-dependent diabetes and sleep apnoe syndrome have been reported to be associated with narcolepsy. Our objective was to explore and possibly confirm the association of narcolepsy and increased BMI. In addition, we addressed the question whether increased BMIs also occur in relatives of narcoleptic patients. Together with narcolepsy-related clinical parameters we measured body weight and height of 132 narcoleptic patients who agreed to parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
58
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(68 citation statements)
references
References 21 publications
8
58
0
2
Order By: Relevance
“…An increased body mass index (BMI) was found in this sample of people with narcolepsy and this is consistent with many other reports [11,12]. While the present study found 86% were overweight or obese (in 2001), the percentage across the Australian population for these BMI categories is 51.8% for females and 67.3% for males [26].…”
Section: Healthsupporting
confidence: 92%
See 1 more Smart Citation
“…An increased body mass index (BMI) was found in this sample of people with narcolepsy and this is consistent with many other reports [11,12]. While the present study found 86% were overweight or obese (in 2001), the percentage across the Australian population for these BMI categories is 51.8% for females and 67.3% for males [26].…”
Section: Healthsupporting
confidence: 92%
“…In terms of health, people with narcolepsy have an increased association with being overweight or obese [11,12] but no studies have considered how their weight may vary longitudinally. There are reports of people with narcolepsy being more prone to also having other physical illnesses, in particular diabetes mellitus [13] and other sleep disorders [14] and it is expected that the incidence of concomitant illnesses would increase with advancing age.…”
mentioning
confidence: 99%
“…The body mass index of narcoleptics is 10% to 20% higher than that of normal controls. 39 The causes of obesity might be related to the hypocretinergic neurotransmission, autonomic nervous system activity, basal metabolism, and the leptin-ghrelin system that is responsible for signaling caloric need, appetite, and satiety. [39][40][41] 6) Obstructive sleep apnea syndrome (OSAS) The prevalence of OSAS is higher in the narcoleptic population (prevalence rates from 9% to 19%) than in the general population.…”
Section: ) Obesitymentioning
confidence: 99%
“…Obesity has been reported in narcolepsy for several decades [4,5,13,27], but this phenotype has not been given much attention. This is partially due to the facts that obesity in narcolepsy can be secondary to reduced daytime activities, and that obesity is only observed in a subset of patients, suggesting that this phenotype may not be the cardinal symptom of narcolepsy.…”
Section: Introductionmentioning
confidence: 99%